2007
DOI: 10.1590/s1517-86922007000200014
|View full text |Cite
|
Sign up to set email alerts
|

Sincronização não-fótica: o efeito do exercício físico aeróbio

Abstract: The main alterations, either acute or chronic, caused by aerobic physical exercise (PE) over the body are generally well-known. However, there is a particular effect of PE which started to be elucidated in the beginning of the 90's in humans which has the capacity to alter the temporal relationship of the body with the environment. The modification of the expression of the circadian rhythms caused by PE qualifies it as a synchronizer of the biological oscillators. The main synchronizer of the biological rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
8
0
6
Order By: Relevance
“…Estudo de revisão de Back et al 24 apontou a AF aeróbica como sincronizador não--fótico, que afeta o sistema de temporização circadiana (STC) por meio de vias não-fóticas, assim podendo adiantar ou atrasar o sono, desta forma, adequando os horários de sono, evitando privação.…”
Section: Discussionunclassified
“…Estudo de revisão de Back et al 24 apontou a AF aeróbica como sincronizador não--fótico, que afeta o sistema de temporização circadiana (STC) por meio de vias não-fóticas, assim podendo adiantar ou atrasar o sono, desta forma, adequando os horários de sono, evitando privação.…”
Section: Discussionunclassified
“…Some elderly choose activities that require less physical effort and frequent naps possibly by having some limitation in functional capacity. (21) Physical inactivity or fatigue may indicate a symptom of depression or physical illness, (22) which can cause social isolation. Some studies have indicated the association between depressive symptoms and naps.…”
Section: Discussionmentioning
confidence: 99%
“…There are medications that can induce the elderly to sleep, such as antihistamines, antidepressants, benzodiazepines, (24) making the elderly to feel unwell for practicing physical activities as a result of excessive daytime sleepiness. (21) The prescription of medicines to the elderly must be accurate and monitored, as some drugs can impair gait and cognition of these subjects, and it may cause drowsiness and indisposition, leading them to physical inactivity. (24) Deleterious effects of frailty, such as loss of physical function and reduced socialization, can negatively affect social activities, physical exercise and exposure to sunlight outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Tem sido utilizada em sistemas de aquecimento de água residencial, em repetidores de telecomunicações, bem como, fornecimento de energia elétrica para equipamentos e dispositivos espaciais. Pesquisas estão sendo realizadas para melhor aproveitamento da energia solar, com enorme potencial de aplicação em larga escala (25) .…”
Section: Espectro Eletromagnéticounclassified
“…Outras variações significativas são previstas por estatística, tal como a incidência média da radiação solar por um período de tempo. Existem ainda os efeitos da formação de nuvens, poluição atmosférica, pó e nevoeiros (4,25) .…”
Section: Horário E Locais De Treinamentounclassified